“His Works Will Live”: Alexander Solzhenitsyn in the Swedish Press of the 1960s - Tatyana V. Marchenko (Studia Litterarum)
Last year the world celebrated the centenary of Alexander I. Solzhenitsyn. However, many sources on the history of translation and reception of his works are overlooked. It seems instructive, in particular, to flip through the central Swedish newspapers, because the writer became a Nobel laureate in an era when the press was the main media force. In the pages of Stockholm’s leading newspapers, Dagens Nykheter and Svenska Dagbladet, the name of Alexander Solzhenitsyn appears at the end of 1962 in correspondence from Moscow highlighting a turning point in Soviet literature — the emergence of One Day Out of Ivan Denisovich. Among Swedish journalists, it is particularly worth noting Sven Walmark, a recognized expert in Soviet Russia, a critic and translator who introduced Solzhenitsyn’s story to the Swedish audience of the 1960s in precise formulas. Solzhenitsyn’s journalistic speeches against censorship also became immediately known and thoroughly referenced in Swedish newspapers. In less than a decade, an unknown Soviet writer grew into a powerful phenomenon of the world literature and world politics in their pages. The article makes emphasis on the perception of Solzhenitsyn’s literary work in Sweden in the reviews ranging from the first mention of his name in the Swedish press to the coverage of the Nobel Prize in literature that was awarded to him in 1970.